2008
DOI: 10.1161/circulationaha.107.698514
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Double-Blind Trial of Darbepoetin Alfa in Patients With Symptomatic Heart Failure and Anemia

Abstract: on behalf of the Study of Anemia in Heart Failure Trial (STAMINA-HeFT) GroupBackground-Substantial evidence suggests that anemia is an independent risk factor for worse outcomes in patients with heart failure (HF). The Study of Anemia in Heart Failure Trial (STAMINA-HeFT) is the largest multicenter, randomized, double-blind, placebo-controlled trial to date evaluating the effect of treating anemia in HF. Methods and Results-Patients (Nϭ319) with symptomatic HF, left ventricular ejection fraction Յ40%, and hemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
181
1
10

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(196 citation statements)
references
References 28 publications
4
181
1
10
Order By: Relevance
“…Although some studies using ESAs performed in single center trials showed improvement of NYHA functional class and echocardiographic data in CHF patients with anemia, 6,7) the latest multicenter randomized, double blind, placebo-controlled trial did not yield the expected results. 8,9) These findings might demonstrate that ESAs alone would be insufficient for improving the oxygenation of heart failure patients with anemia.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Although some studies using ESAs performed in single center trials showed improvement of NYHA functional class and echocardiographic data in CHF patients with anemia, 6,7) the latest multicenter randomized, double blind, placebo-controlled trial did not yield the expected results. 8,9) These findings might demonstrate that ESAs alone would be insufficient for improving the oxygenation of heart failure patients with anemia.…”
Section: Discussionmentioning
confidence: 96%
“…Although several reports demonstrated the benefit of ESAs in CHF patients who had declining NYHA functional classes or increasing contractions of the left ventricle, 6,7) a few reports did not reveal any definite clinical benefit of ESAs in CHF patients. 8,9) Hence, effective pharmacotherapy for CHF with anemia is still unclear.…”
mentioning
confidence: 99%
“…Результаты другого мета-анализа (7 исследова-ний, 650 больных) также продемонстрировали безопас-ность использования рекомбинантного ЭПО (рЭПО) при ХСН [17]. Однако в исследовании STAMINA-HeFТ использование дарбопоэтина альфа не привело ни к повы-шению переносимости физической нагрузки, ни к умень-шению ФК ХСН, ни к улучшению качества жизни [18].…”
Section: Discussionunclassified
“…Sin embargo, dos estudios controlados 29,30 , uno con poco más de 300 pacientes, y el otro con 2728 y 28 meses de seguimiento, no resultaron en diferencia significativa alguna entre el tratamiento con darbapoyetina alfa (eritropoyetina sintética de segunda generación) o placebo, además de la demostración del aumento de riesgo a sufrir eventos cerebrovasculares en este grupo de pacientes 31 . Con ellos se cierra el capítulo de la posible utilidad terapéutica de los AEE en IC.…”
Section: Tratamiento Del Déficit De Hierro En La Icunclassified